PERSUASIVE LANGUAGE FEATURES ON MULTIMODAL TEXT OF INDONESIAN VERSION OF ORIFLAME PERFUME CATALOGUE OF JULY 2014 EDITION - ULFA, MARIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: discourse analysis, multimodal text, mode, Indonesian version of Oriflame perfume catalogue, persuasive language. Advertisement is applied to persuade the viewer within several modes. Therefore, advertiser should consider attracting images and persuasive texts. The writer conducts a study concerning on some theories of persuasive language features proposed by Lakoff (1982) about linguistic novelty, Geis (1982) about linguistic techniques, and Searle (1999) about speech acts. The problem of the study is what the features of persuasive language related to multimodal texts on Indonesian version of Oriflame perfume catalogue of July 2014 edition are.This study used qualitative approach in relation to the use of phenomenon descriprion. It is included into document analysis because it is applied in written advertisements by analyzing the texts.The present study reveals that within four multimodal advertisements, there are ten findings about absence of subjects and verbal auxiliaries, eight uses of semantic anomaly, and two uses of pragmatic novelty, seven uses of imperative structures, one term of announcing, one rhetorical question, one elliptical comparative, one finding of constituting product name, seven assertives, eight directives, one expressive, and one declarative. It is shown that all of advertisements employ all theories of persuasive language features. It indicated that advertiser considers the strategy and effectiveness of persuasive language features in order to obtain act of the reader to purchase a particular product.The writer suggests for the next researchers who will conduct a study about persuasive language feature to employ the other aspects in analyzing the text, like stylistic analysis, word formation process, and language functions.